Analysis of Ecotourism Attractions Management in Pelangi Agrotourism, Metangor Village, Kulim District, Pekanbaru City - Silfani, Novri; Eka Asih Febriani; Ismail; Dewi Ramadhan; Rosmadi bin Fauzi (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
This study aims to analyze the management of ecotourism attractions at Agrowisata Pelangi located in Metangor Village, Kulim District, Pekanbaru City. The focus of this study is tourism management, tourism facilities, the impact of sustainable tourism. This study uses a descriptive qualitative research method. Data collection techniques are observation, interviews, and documentation. The results of the study indicate that the management of ecotourism attractions at Agrowisata Pelangi relies on educational tourism which has been running quite well. Although it has succeeded in attracting tourists, improvements are needed in the facility aspect which must be consistent in the maintenance and development of facilities and strengthening cooperation with the government for the development of sustainable tourism.